(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: Initial management of diabetic patients is very crucial for the future outcome. Objective: The purpose of the present study was to see the initial management pattern of diabetes mellitus patients. Methodology: This cross sectional study was conducted in different diabetic centers in Bangladesh from August 2015 to October 2016 for a period of more than one year. All the diabetic patients at any age with both sexes were included in this study. The diabetic patients were interviewed face to face. The initial treatment modalities were collected from the diabetic guide book from all the patients. Result: A total number of 482 diabetic patients were recruited for this study. In most patients (n=451) glycemic status was the determinant of initial treatment regimen. In 18 patients, regimens were chosen due to complication, 10 for infection and 3 for surgery. Life style with diet was advised in 10(58.82%) cases, 29(9.6%) cases and 3(1.84%) cases in less than 8.3 mg/dL, 8.3 to 13.9 mg/dL and more than 14.0 mg/dL group of FPG respectively. Considering monotherapy metformin was given in 5(29.41%) cases, 119(39.4%) cases and 26(15.95%) in less than 8.3 mg/dL, 8.3 to 13.9 mg/dL and more than 14.0 mg/dL group of FPG respectively. Conclusion: In conclusion the initial treatment pattern of diabetes mellitus patients is varied in different diabetic centres of Bangladesh. Sir Salimullah Med Coll J 2022; 30: 3-8